ANALISIS DAMPAK PENGGUNAAN E- MONEY, E- WALLET DAN PENGGUNAAN ATM TERHADAP PERPUTARAN EKONOMI DI MASYARAKAT - Rindi Astika Yuliana; Galuh Kusuma Ningtantri, Kristina Samca Susi, Sugiyanto (ADISAM PUBLISHER, 2024)
This research aims to analyze the extent to which the use of e-money, e-wallet and also the use of ATM machines in Indonesia has a big impact on the economic behavior of modern society. Almost all Indonesian people spend their shopping time by taking advantage of advanced technology, namely by using online payment systems, for example, for transportation users such as trains, toll road users, they mostly use e-money, then people who are used to shopping at market places often use e-money. wallet for transactions, or just to buy credit or pay electricity bills. The existence of ATM machines at almost every point in Indonesia really means that the circulation of electronic money is very large, but in reality there are still many people in our society who do not have money or have low financial capabilities. This is a problem. Therefore, the author tries to analyze this using qualitative descriptive methods, literature reviews and/or literature studies that are relevant to the problem theme related to the impact of the widespread distribution of e-money, e-wallets and ATM machines in the community. One of the positive impacts of using electronic money is to prevent inflation and reduce the circulation of paper money, people also become safer without having to carry paper money everywhere, however education on the use of electronic money among the public must also be improved, considering that ease of transactions can also cause society is becoming increasingly consumerist, and is also very susceptible to hackers if personal data leaks occur. A nation that wants to be independent and advanced on an economic scale must be open to current developments, including being open to an online financial system, but the government must also have control and balancing regarding these regulations and the community's economic circulation, so that there are no social gaps between communities from an economic perspective.